FLASH (FUN LEARNING ENGLISH) WITH PICTIONARY FOR VOCABULARY ENAHNCHING ON RURAL STUDENTS - Sartika Dewi Harahap (Journal of English Education and Linguistics, 2021)
Learning English for some students were getting bored and less fun. It makes them become lazy and unserious to following the class. Especially, in rural students with local language user for learning the foreign language. Teaching English will become the difficult way for English teacher who teach in seven grade students on MTs S Ittihadiyah Aek Korsik Desa Parimburan Kecamatan Sungai Kanan Kabupaten Labuhanbatu Selatan North Sumatera. Vocabulary is the basic and the important aspect of language in order to easier to able to speak, to read, to write and to listen. FLASH (Fun Learning English) with Pictionary as a teaching strategy were designed and adapted by English teacher. It can help the students feel comfortable, fun, active and more motivated when they were enhaced their vocabulary during the learning process. The author conducted the data by using classroom observation and test including a series of processes to identify the problem that are appearing. The analysis showed how the pictionary gave the enhancing the students on knowing, memorizing and pronouncing the word. Keywords : Pictionary, Vocabulary, Fun Learning English.